PENGARUH VARIABEL MAKRO EKONOMI TERHADAP INDEKS HARGA SAHAM GABUNGAN TAHUN 2018-2022 - Daulay, Diah Hanifah; Siregar, Riski Perdimansyah (Journal of Management, Economic and Accounting (JMEA), 2025)
Economic development in a more advanced direction will open people's minds to a more modern direction, including in investing the funds they have. The capital market is a financial instrument that buys and sells securities. The Indonesian Stock Exchange (BEI) is a capital market owned by Indonesia. The index in the capital market functions as an indicator of market trends, meaning that the stock index functions to determine whether current market conditions are active or sluggish. The macroeconomic environment is the environment outside the company that is able to influence the company's daily operations. This research has an associative nature, which aims to evaluate the relationship between two or more variables. The focus of this research is to examine the influence of macroeconomic variables on the value of the Composite Stock Price Index (IHSG), using annual data from 2018 to 2022 on the Indonesian Stock Exchange. This research was conducted at the Indonesian Stock Exchange (BEI) and focused on the Composite Stock Price Index (IHSG) as the research object. The duration of the research covers a five year period, namely from 2018 to 2022, which is used to research the IHSG. This research utilizes IHSG closing price data per year from 2018 to 2022. Annual IHSG data is taken by calculating the average daily closing price of IHSG every month during that period, which is measured in percentages. This research involves a population of all publicly traded companies listed on the Indonesian Stock Exchange every year. The sampling method used was census sampling, where all elements of the population were included in the research. Based on the SPSS processed results, the t1 value was -1.834. The t1 value of -1.834 is smaller than the ttable of -1.703, so H1 is accepted while H0 is rejected so it can be concluded that interest rates have a negative and significant effect on the IHSG. The second macro variable, namely inflation, has a t count of 0.092. The t2 value of 0.092 is greater than ttable of -1.703, so H0 is accepted while H1 is rejected, so the conclusion is drawn that partially inflation has no significant effect on the IHSG. The third macro variable, namely the money supply, has a t count of 3.189. The t3 value of 3.189 is greater than ttable of 1.703, so H1 is accepted while H0 is rejected so that it can be partially concluded that the money supply has a positive and significant effect on the IHSG. The fourth macro variable, namely GDP, has a t count of 0.718. The t4 value of 0.718 is smaller than the t table of 1.703, so H0 is accepted while H1 is rejected, so it can be concluded that GDP does not have a significant effect on the IHSG. Based on hypothesis testing and the discussion in the previous chapter, it can be concluded that interest rates, inflation, money supply and GDP influence the IHSG simultaneously. Partially, interest rates have a significant negative effect on IHSG. The money supply partially has a significant positive effect on the IHSG. Meanwhile, inflation and GDP partially do not have a significant effect on the JCI. Based on research data, the inflation rate in Indonesia from 2018 to 2022 is still not classified as high level inflation so stock prices are not too influenced by the inflation rate. The Central Statistics Agency only records formal economic activity as a calculation of Indonesia's GDP level so that GDP figures in Indonesia cannot yet show all economic activity in Indonesia. Administrative weaknesses are the cause of limitations in recording informal activities in developing countries like Indonesia. The structure of economic activity in Indonesia which is dominated by informal and agricultural activities is also the cause of limited recording capabilities so that when GDP increases it does not necessarily mean that the per capita income of each individual increases so that investment patterns in the capital market are not affected by an increase in PDB.